Cost of treatment as a barrier to access and continuity of healthcare for patients with mental ill-health in Lagos, Nigeria - Olufemi B. Olugbile; Ayodele O. Coker; Mathew P. Zachariah (PAGEPress Publications, 2013)
In Nigeria, there are several barriers to access to effective mental healthcare, e.g. cost, distance to the mental health facility, social stigma, cultural beliefs, attitudes and taboos. This study aimed at i) determining the cost of treatment of a random sample of psychiatric patients and to compare the sample with a matched group of patients from the internal medical department clinics; ii) assessing the impact of cost on access to care and maintenance treatment for the study group in the context of their exclusion from the Lagos State free health services and the National Health Insurance Scheme. Medical records of 100 patients currently attending the outpatients’ clinic of the Department of Psychiatry of the Lagos State University Teaching Hospital (Ikeja, Nigeria) were randomly selected and audited. A similar exercise was also conducted for patients attending the medical outpatients’ clinic in the same hospital. The monthly costs of prescribed medications were computed and compared. The monthly cost of treatment of patients from the Department of Psychiatry compared to patients with physical ailments from the medical outpatients’ clinic was found to be significant vis à vis the average income of average Nigerians. Contrary to expectations, the mean cost of drug treatment borne by medical outpatients was much higher (N=2549.07 vs N=1904.5) (P<0.05) than that of patients attending the psychiatric outpatients’ clinic. However, the expensive cost for the psychiatric patients far exceeded the expensive costs for the medical patients. The findings from this study showed that the average monthly cost of treatment of patients attending the psychiatric clinic was lower than patients from the medical outpatients’ clinic. However, the most expensive cost for psychiatric patients far exceeded the most expensive cost for medical patients. This study also revealed that there is no free health program covering psychiatric treatment anywhere in Nigeria and mental health drugs are funded from personal and family expenses. It is thereby suggested that policy makers should change policy regarding the coverage of Nigerians with mental illness. In doing so, the major barrier to assess and the treatment gap can be reduced.